Hematoxylin assay of cupric chelation can give false positive results - Macáková, Kateřina; Catapano, Maria Carmen; Tvrdý, Václav; Klimková, Kateřina; Karlíčková, Jana; Mladěnka, Přemysl (Journal of trace elements in medicine and biology, 2019)
Some compounds without apparent chelation sites have been shown to chelate cupric ions using the hematoxylin assay. Since these compounds also have reduction potential (direct antioxidant effect), the aim of this study was to determine the possible interference of reducing agents with the hematoxylin assay. Four different known reducing agents (hydroxylamine, vitamin C, trolox - a water-soluble form of vitamin E and reduced glutathione /GSH/) were selected for the study together with oxidized glutathione (GSSG) for comparison. All tested compounds behaved as cupric chelators in the spectrophotometric mildly competitive hematoxylin assay. In-depth analysis however showed that only GSH and GSSG were able to form complexes with both cupric and cuprous ions and only GSSG partly retained copper in its complexes in the more competitive bathocuproine assay. Further experiments showed that with the exception of GSSG, all other compounds reduce Cu2+ ions. Conclusion: Compounds reducing copper such as antioxidants can give false positive results in the hematoxylin-screening assay. GSSG is a stronger Cu chelator than GSH and does not reduce Cu, in contrast to the latter and thus may be a protective element after oxidation of GSH.
Keywords: falešně pozitivní reakce; molekulární konformace; chelátory; měď; Molecular Conformation; Complex; Stoichiometry; Hematoxylin; Chelating Agents; False Positive Reactions; hematoxylin; Copper; Glutathione